Time to be brave - Runton, Andy (New York, NY Graphix, an imprint of Scholastic, 2021)
"For Owly and Wormy, nothing beats the power of friendship! But fear can be a powerful force, too. There's a new visitor to the forest, an opossum who's misunderstood because of the way he looks. Wormy is afraid of him, and when Owly tries to untangle him from a fence, Possey begins hissing and bares his sharp teeth ... Can the trio be brave and face their fears with just a little courage and a lot of friendship?"--
Chiefly illustrations.
112414
Keywords: Owls -- Comic books, strips, etc; Opossums -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Fear -- Comic books, strips, etc; Individuality -- Comic books, strips, etc; Animals -- Fiction; Cartoons and comics; Juvenile Fiction -- Comics & Graphic Novels -- Action & Adventure; Juvenile Fiction -- Comics & Graphic Novels -- Humorous; Juvenile fiction; Comic books, strips, etc; Juvenile works; Fiction; Animal fiction; Comics (Graphic works); Funny animal comics; Graphic novels; Humorous comics